Helath iconography in the Bishopric of Trujillo (1782-1785) - Victorio Cánovas, Emma Patricia (2021)
This note aims to visualize the health problems in the Peruvian viceroyalty based on the graphic information provided by the repertoire of watercolors commissioned by Bishop Martínez Compañón during his visit to his jurisdiction in northern Peru, between 1782 and 1785. The intention is also to analyze the referred representations in the watercolors to understand in a general way the ravages caused by diseases and epidemics in the population, in addition to the official and popular medical solutions that were used at that time; and also, to understand the effort of these anonymous popular artists for the graphic representation of these evils.